Enhanced Efficiency and Stability of Perovskite Solar Cells Through Nd‐Doping of Mesostructured TiO2. Issue 2 (3rd December 2015) - Roose, Bart; Gödel, Karl C.; Pathak, Sandeep; Sadhanala, Aditya; Baena, Juan Pablo Correa; Wilts, Bodo D.; Snaith, Henry J.; Wiesner, Ulrich; Grätzel, Michael; Steiner, Ullrich; Abate, Antonio
Abstract : Block‐copolymer templated chemical solution deposition is used to prepare mesoporous Nd‐doped TiO2 electrodes for perovskite‐based solar cells. X‐ray diffraction and photothermal deflection spectroscopy show substitutional incorporation into the TiO2 crystal lattice for low Nd concentration, and increasing interstitial doping for higher concentrations. Substitutional Nd‐doping leads to an increase in stability and performance of perovskite solar cells by eliminating defects and thus increasing electron transport and reducing charge recombination in the mesoporous TiO2 . The optimized doping concentration of 0.3% Nd enables the preparation of perovskite solar cells with stabilized power conversion efficiency of >18%. Abstract : Neodymium doping of TiO2 is shown to be an effective way to increase perovskite solar cell performance. Efficiency is enhanced by the passivation of deep trap states, leading to reduced recombination and increased transport. Stability is simultaneously enhanced by the elimination of oxygen defects.